2008
DOI: 10.1227/01.neu.0000311066.03121.b8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Tractography Predicts Motor Functional Outcome in Patients With Spontaneous Intracerebral Hemorrhage

Abstract: Motor functional outcome in patients with intracerebral hemorrhage can be predicted by measuring FA values using diffusion tensor tractography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 25 publications
7
75
0
Order By: Relevance
“…10,11,13,23 They reported that the FA in the affected pyramidal tract was reduced 13%-32% during the subacute-to-chronic phase of an ischemic stroke, and the reductions in the FA were more severe at later time points of 2 days to 1 year. 10,11,12,29 Yoshida et at 14 reported that the FA ratio in the affected side decreased 20% within 5 days after the onset. In the present study, the FA decreased by 11% in the affected cerebral peduncle with an unchanged MD within 2 days after the onset of an ICH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,13,23 They reported that the FA in the affected pyramidal tract was reduced 13%-32% during the subacute-to-chronic phase of an ischemic stroke, and the reductions in the FA were more severe at later time points of 2 days to 1 year. 10,11,12,29 Yoshida et at 14 reported that the FA ratio in the affected side decreased 20% within 5 days after the onset. In the present study, the FA decreased by 11% in the affected cerebral peduncle with an unchanged MD within 2 days after the onset of an ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the FA is accurate at a single fiber and is affected by the crossing fibers because of the partial volume effect in the voxel. This phenomenon is known as the pseudodiffusion anisotropy decrease, 14 which may lead to the underestimation of anisotropy in the lesion. The pyramidal tract usually represents both the corticospinal tract and The patients are divided into good and poor on the basis of the score of the PG evaluated at the 28th day, and the ratio of the FA is plotted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,20,22,27) DTI can sensitively detect the direction of diffusion of water molecules and so reveals the orientation of the white matter tracts. 36) This anatomical detail enables clinically useful characterization of the degeneration of neural fibers affected by various neural diseases. 37) Recent studies based on fractional anisotropy (FA) values in some brain regions, including the corpus callosum and corticospinal tracts, have reported that patients with INPH exhibit white matter changes.…”
Section: Dti Of Inphmentioning
confidence: 99%
“…Recovery of an injured CST is mandatory for good motor recovery after ICH, and degeneration of an injured CST accompanies poor motor function in patients with ICH. [2][3][4][5][6] Therefore, elucidation of the CST state is an important topic for rehabilitation in patients with ICH.…”
mentioning
confidence: 99%